Diet alters species recognition in juvenile toads - Pfennig, Karin S. (The Royal Society, 2013)
Whether environmental effects during juvenile development can alter the ontogeny of adult mating behaviour remains largely unexplored. We evaluated the effect of diet on the early expression of conspecific recognition in spadefoot toads, Spea bombifrons. We found that juvenile toads display phonotaxis behaviour six weeks post-metamorphosis. However, preference for conspecifics versus heterospecifics emerged later and was diet dependent. Thus, the environment can affect the early development of species recognition in a way that might alter adult behaviour. Evaluating such effects is important for understanding variation in hybridization between species and the nature of species boundaries.